High SOX8 expression promotes tumor growth and predicts poor prognosis through GOLPH3 signaling in tongue squamous cell carcinoma. (19th April 2020) - Chen, Shuwei; Li, Huan; Li, Xiyuan; Chen, Wenkuan; Zhang, Xing; Yang, Zhongyuan; Chen, Zhipeng; Chen, Jingtao; Zhang, Ying; Shi, Dingbo; Song, Ming
Abstract: According to our previous study, GOLPH3 is markedly up‐expressed in tongue squamous cell carcinoma (TSCC), which is also associated with poor survival. However, it remains unclear about key upstream and downstream mechanisms of GOLPH3. This study aimed to illuminate new mechanisms modulating GOLPH3 upregulation and promoting TSCC development at the molecular level. Using mass spectrometry and agarose‐streptavidin‐biotin pull‐down analyses, SOX8 (SRY‐Box 8) was identified to be the new protein to bind the GOLPH3 promoter within TSCC cells, which was further verified to be the regulator of GOLPH3 upregulation. The knockdown of SOX8 suppressed the promoter activity of GOLPH3, while secondarily inhibiting TSCC cell proliferation both in vivo and in vitro. Interestingly, GOLPH3 overexpression rescued the SOX8 knockdown‐mediated suppression on TSCC proliferation. Additionally, exogenous over‐expression of SOX8 also activated the activity of promoter as well as GOLPH3 expression, in the meantime of promoting TSCC development. Moreover it was discovered that SOX8 regulated GOLPH3 expression through interacting with TFAP2A. Moreover our results suggested that the SOX8 level was increased within tumor tissue compared with that in para‐cancer normal counterpart, which showed positive correlation with the GOLPH3 level. According to Kaplan‐Meier analyses, TSCC cases having higher SOX8 and GOLPH3 expression were associated with poorer prognostic outcomes. Taken together, this study reveals that SOX8 enhances the TSCC cell growth via the direct transcriptional activation of GOLPH3, which also indicates the potential to use SOX8/GOLPH3 pathway as the treatment target among TSCC patients. Abstract : SOX8 promotes TSCC cell growth and predicts poor prognosis via the direct transcriptional activation of GOLPH3 expression, which suggests that the SOX8/GOLPH3 pathway may be a potential therapeutic target for TSCC patients.